Lā. Ca. Rā - Rāmāmirutam, Lā. Ca.,Tilakavati (Amrutā, 2007)
Collection of short stories on social themes
Short stories. - Tamil in Tamil-Schr. - Taricaṉam – Kaṟaipaṭṭa ilai – Mahāpali – Tīpak – Maṇ – Taṉmāṉam – Itaḻkaḷ – Rāma Tarmam – 14 ? – Metteṉṟu oru muttam – Rāk viḷampit Apirāmi
Keywords: Short stories; Tamil